Efficacy of Lycium barbarum (Goji berry) mouthwash for managing periodontitis: a randomized clinical trial [version 4; peer review: 2 approved, 1 approved with reservations] - Laasya Shettigar; Aditi Chopra; Richard Lobo; Amee Sanghavi; Shobha Ullas Kamath; Prajna P Nayak; Ashmeet Shah; Usha Y Nayak; Mangalore Shravya S; Padmaja A Shenoy; ShivaPrasada Gadag (F1000Research)
Background Removal of the microbial deposits (plaque and calculus) by performing effective scaling and root planing (SRP) is the fundamental step for managing periodontal disease (gingivitis and periodontitis). Various adjuncts in the form of mouthwash, gels, and toothpaste are also being used as adjuncts to SRP for managing periodontitis. Recently, Lycium barbarum (L. barbarum), commonly known as goji berry or wolfberry, has gained popularity for managing chronic inflammatory and infectious diseases. However, its efficacy in managing periodontitis has never been explored. Hence the present study aims to evaluate the efficacy of goji berry mouthwash compared to chlorhexidine mouthwash for managing periodontitis. Methods 60 adult participants were divided randomly using computer-generated random sequences into two groups (case group: L. barbarum mouthwash (Males: 16; Female: 14); control group: 0.2% chlorhexidine gluconate mouthwash (Males: 14; Females: 16)). The changes in the gingival index (Gi), plaque index (Pi), bleeding on probing (BOP), clinical attachment loss (CAL), probing pocket depth (PPD), microbial load, and antioxidant levels (protein thiol) in saliva were noted at the baseline, at 15 days and one month. Results A significant reduction in the mean PPD, Pi, BOP, and Gi was seen from baseline to one month in both the control (P-value=0.006, 0.027, 0.000, and 0.036 respectively) and test groups (P-value=0.035, 0.000, 0.034, and 0.000 respectively). However, the antioxidant levels (protein thiol) in saliva were significantly increased only in the test group. Conclusion Goji berry mouthwash along with SRP reduced the Gi, Pi, BOP, and PPD in patients with periodontitis. However, no statistically significant difference was noted between the use of goji berry and chlorhexidine mouthwash. Goji berry mouthwash was more effective than chlorhexidine in increasing the antioxidant levels in saliva.